Assessing the Impact of Inclusive Education on Children with Disabilities in Kisoro Municipality. - Tusingwire, Hope (Kabale University, 2024)
The study assessed the impact of inclusive education on children with disabilities in Kisoro Municipality. The objectives of the study were; to assess the socio-cultural factors affecting the use of inclusive education on children with disabilities in selected primary schools of Kisoro Municipality.to examine the economic factors affecting use of inclusive education on children with disabilities in selected primary schools of Kisoro Municipality and to examine the environmental factors affecting inclusive education on children with visual impairment in selected primary schools of Kisoro Municipality. The findings of the study revealed that most of the respondents were between the ages of 18 and 25 years. Teachers, parents, caregivers and children mentioned hearing impairment, visual and speech difficulty. A much smaller percentage (50-65%) mentioned learning and multiple difficulties. Very few respondents (1-5%) could mention other types of disability like autism, or mental disabilities. The study concluded that the concept of all-inclusive education means welcoming all children, without discrimination, into regular or ordinary schools. Indeed, it is a focus on creating environments responsive to the differing developmental capacities, needs, and potentials of all children. Inclusion means a shift in services from simply trying to fit the child into 'normal settings'; it is a supplemental support for their disabilities or special needs and promoting the child's overall development in an optimal setting. It calls for respect for differences and diversity of individual characteristics and needs. This has to include a consideration of overall organization, curriculum, classroom practice, support for learning, and staff development. The study recommended that In the schools studied, the number of teachers was between 0-2. Sometimes a teacher with special needs would be allocated to certain class and it would be impossible to give support to other children in other classes. The government should include a module on Special needs in the training of all teachers so that they all know what to do. The teachers need to be equipped with the concept of all-inclusive education in order to understand the differences between children with and without disabilities. Such opportunities would help teachers understand that all children can learn if they are given the chance.